2021
DOI: 10.3390/antibiotics10101143
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Endolysin-Based Treatments against Gram-Negative Bacteria

Abstract: The prevalence of multidrug-resistant Gram-negative bacteria is a public health concern. Bacteriophages and bacteriophage-derived lytic enzymes have been studied in response to the emergence of multidrug-resistant bacteria. The availability of tRNAs and endolysin toxicity during recombinant protein expression is circumvented by codon optimization and lower expression levels using inducible pET-type plasmids and controlled cultivation conditions, respectively. The use of polyhistidine tags facilitates endolysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…However, as with all other endolysins acting on Gram-negative bacteria, cells were treated with EDTA which binds and removes divalent ions that stabilize the surface structure of cells, thus resulting in a partially destabilized outer membrane. Other published studies have reported the use of such compounds to study the activity of the enzymes against Gram-negative bacteria ( 31 ). While the use of chemicals such as EDTA is medically not possible, the key aspect of studies such as ours and previously reported research is the activity of the enzyme per se , albeit in concert with EDTA.…”
Section: Discussionmentioning
confidence: 99%
“…However, as with all other endolysins acting on Gram-negative bacteria, cells were treated with EDTA which binds and removes divalent ions that stabilize the surface structure of cells, thus resulting in a partially destabilized outer membrane. Other published studies have reported the use of such compounds to study the activity of the enzymes against Gram-negative bacteria ( 31 ). While the use of chemicals such as EDTA is medically not possible, the key aspect of studies such as ours and previously reported research is the activity of the enzyme per se , albeit in concert with EDTA.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may lend itself to the use of endolysin cocktails which can target several BV-associated anaerobes, in a similar fashion to the approach used in bacteriophage therapy [ 40 ]. However the development of endolysins against P. bivia and other Gram-negative bacteria represents a continual challenge in the field [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as with all other endolysins acting on Gram-negative bacteria, cells were treated with EDTA which binds and removes divalent ions that stabilize the surface structure of cells, thus resulting in a partially destabilized outer membrane. Other studies reported have also employs such compounds to study the activity of the enzymes against Gram-negative bacteria (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, as with all other endolysins acting on Gram-negative bacteria, cells were treated with EDTA which binds and removes divalent ions that stabilize the surface structure of cells, thus resulting in a partially destabilized outer membrane. Other studies reported have also employs such compounds to study the activity of the enzymes against Gram-negative bacteria (33). While the use of chemicals such as EDTA is medically not possible, the key aspect of studies such as ours and previously reported research is the activity of the enzyme per se, albeit in concert with EDTA.…”
Section: Discussionmentioning
confidence: 99%